2012
DOI: 10.1016/j.jviscsurg.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of incisional hernia. State of the art in 2012

Abstract: Laparoscopic repair of ventral incisional hernia is technically feasible and reliable for large hernia defects, even in obese patients. This approach should be reserved for patients with no history of previous hernia repair in order to avoid the risk of intestinal injury. It appears to allow for a shortened duration of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
11
2
2
Order By: Relevance
“…All these patients were treated by laparoscopic repair, but no specific data have been reported [11,103]. In other studies with a lower level of evidence, all the reported recurrences were approached by laparoscopy [18,44,51,107,133].…”
Section: Recurrent Ventral/incisional Herniamentioning
confidence: 98%
See 4 more Smart Citations
“…All these patients were treated by laparoscopic repair, but no specific data have been reported [11,103]. In other studies with a lower level of evidence, all the reported recurrences were approached by laparoscopy [18,44,51,107,133].…”
Section: Recurrent Ventral/incisional Herniamentioning
confidence: 98%
“…Several randomized controlled studies and meta-analysis of controlled trials published in the last decade have demonstrated that laparoscopic repair should be considered a safe technique, and there is a sufficient follow-up to state that most of the barrier mesh prostheses determine a very low risk when placed intraperitoneally [11,36,61,103].…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations